Faktor-Faktor Kualitas Pelayanan Yang Mempengaruhi Kepuasan Pasien Kelas II di RSUD Batara Siang Pangkep - Frida Yuanita (Universitas Muhammadiyah Manado, 2019)
Satisfaction is the level of condition that is felt to be in accordance with the patient's expectations. Audit data on perceptions of satisfaction in 2018 stated that in class II inpatients there was 40.5% dissatisfaction with nurses' attitudes, 37.1% nursing actions, and 51.7% cleanliness. To determine the factors that influence patient satisfaction in class II inpatient rooms at Batara Siang Pangkep Regional Hospital. The research design is descriptive narrative. The patient population is all inpatients, class III at Batara Siang Pangkep Hospital, the average number of patients is 200 patients/month, the population in one week is 50 patients. The sampling technique was purposive sampling, the number of respondents was 44 people. Univariate analysis results show that patients are satisfied with reliability 68.2%, patients are less satisfied with responsiveness 52.3%, patients are satisfied with assurance 61.4%, patients are satisfied with empathy 54.5%), patients are satisfied with tangibles 60.4%. shows that patients are less satisfied with, nurses do not provide special time to help patients (walking, urinating/defecating) 68.2%, patients are less satisfied, nurses do not prepare medication that must be taken 61.4%, nurses do not ask enough about the patient's appetite 53 .3%, and patients are not satisfied. The bathroom floor in the room is not clean, slippery and smells 50%. Suggestions for increasing patient satisfaction, especially responsibility in this case, must pay attention to personal hygiene and patient medication administration.